Evaluation of controlled-release triamcinolone acetonide-loaded mPEG-PLGA nanoparticles in treating experimental autoimmune uveitis. (14th February 2019) - Guo, Dadong; Li, Qin; Sun, Yuanyuan; Guo, Junguo; Zhao, Qing; Yin, Xuewei; Wei, Huixia; Wu, Shanshan; Bi, Hongsheng
Abstract: Uveitis is a recurrent, sight-threatening intraocular inflammatory disease and is treated with glucocorticoids in clinical practice. In the present study, methoxypoly(ethyleneglycol)-poly(dl-lactide-co-glycolic acid) (mPEG-PLGA) nanoparticles in combination with triamcinolone acetonide (TA) were fabricated using a modified double emulsification method. Further, we characterized the TA-loaded nanoparticles, and investigated the effects of TA-loaded nanoparticles on experimental autoimmune uveitis rats, including histopathological examination and the alterations in interleukin (IL)-17 and IL-10 at mRNA and protein levels in either aqueous humor or serum. As a result, the TA-loaded nanoparticles were a well-defined spherical shape with a mean particle size of 82 nm. The in vitro release profile showed that the TA-loaded nanoparticles could sustain for more than 45 days, and possessed higher anti-inflammatory effects compared to TA alone after pathological examination, resulting in decreased IL-17 and elevated IL-10 levels in both aqueous humor and serum. Based on these findings, it can be concluded that TA-loaded mPEG-PLGA nanoparticles can potentially provide a better anti-inflammatory effect in treating chronic and recurrent uveitis in clinical practice.